Limits and shortcomings of market mechanisms to protect biodiversity and ecosystem services - Giani Gradinaru (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
Biodiversity crisis is one of the many crises that started at the turn of the millennia. The strategy of action outlines a strong economic component, together with the recognition of market mechanisms as the most effective policies to protect biodiversity. In this context, biodiversity and ecosystem services are natural assets that play a key role in economic strategies to promote development and prosperity. With a view to identifying the main business opportunities that may be associated with the ecosystems services, our scientific approach and analysis has primarily focused in the first stage on the inter-connection between the economic mechanisms and the ecosystems services, thus aiming at substantiating the viability of existing relationship. For that purposes, we have analyzed the implementation methods and techniques of nature conservation policies. The concepts underlying the economic expression of the value of ecosystems services have thus (been) formed and developed. Developing market mechanisms for nature conservation purposes has become a significant trend growing stronger and faster each and every year. Although controversies and disputes still stir and leading to an obvious split between opponent supporters of conflicting opinions, both international organization and national governments acting either independently or in concert have initiated and implemented such mechanisms. The second part of our paper sets out the main business patterns that can be developed so as to fit into the triple referential requirements for a sustainable development (through the positive effects they create on three distinct dimensions): create profit (economic-wise), contribute to protection of bio-diversity (environment-wise) and helps out the equitable distribution of benefits (social-wise). Finally, points out that markets fail to quantify the value of most ecosystem services. Existing price signals reflect at best, only a proportion of the total amount corresponding provision of food, water or fuel.
Keywords: 650; ecosystem services; green innovation; entrepreneurship; business opportunities